Blogging as an EFL Practice Beyond The Classroom - Amado Cepeda, Rosa María (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This small research project aims to explore how the use of a blog can benefit students’learning processes in a rural school. Materials such as texts, videos, and even links for connecting with other similar sites were provided to students in order to employ blogs as a language exposure platform forEnglish learning. Data was collected by means of students’ narratives (opinions) regarding their use of the blogs and informal observation of students’ engagement in the process andof their artifacts. As a result,findings indicate that the use of blogs became a useful aid to support language learning due to the contact participants established with the foreign language in the learning process, incidentally blogging enhanced students’ participation and interest in their own learning